'How's the Service?' A Study of Service Quality Perceptions across Sectors and Source Markets. (29th December 2011) - Ayeh, Julian K.; Chen, Rose Xiaying
ABSTRACT This study assessed the performance of the hotel, retail and travel agency sectors in Hong Kong. The importance–performance analysis (IPA) model and various statistical techniques were employed to examine visitors' cognition of the importance and performance of pertinent service quality attributes and to better understand the factors that may influence their overall satisfaction across different sectors and source markets. Whereas the multivariate analysis of variance and analysis of variance tests suggest no significant differences in service quality perceptions across the three sectors, the IPA revealed that these sectors differ qualitatively in terms of which service quality attributes are most critical. The findings further suggest a negative relationship between cultural distance and satisfaction with Asian tourists being less satisfied than their non‐Asian counterparts. The results hold important managerial implications for resource allocation and service quality improvement in specific areas. Copyright © 2011 John Wiley & Sons, Ltd.